Detection Method Based on RFID Tag on the Metal Surface. Issue 1 (1st December 2022) - Zhang, Shuang; Gong, Yuxin; Zhu, Guokai
Abstract: In radio frequency identification (RFID) technology, RFID tags' work on the metal surface is greatly affected by the metal, and the read/write distance and read rate of the tag will be reduced along with the change of the distance between the tag and the metal surface. Aiming at this feature, this paper studies and designs two kinds of metal-resistant UHF RFID micro-strip tags with a center frequency of 915MHz according to the "resonant cavity principle" and HFSS simulation software. After optimization, the size of the tag antenna is reduced. Through the distance expression and experiment, we verify the maximum recognition distance between the reader, and the tag can reach 3.46m, which can solve the problem of conventional RFID tags by metal interference.